Reinterpreting Kafā’ah: The Interaction of Islamic Legal Norms and Social Realities in Contemporary Indonesian Marriage Practices. - Deri Eka Putra; Era Zufialina; Azka Ummah; Doni Prananda (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This study examines the concept of kafā’ah (compatibility) in marital partner selection within the Indonesian context, focusing on the interaction between Islamic legal norms and evolving social realities. Although classical Islamic jurisprudence emphasizes religious and moral compatibility as primary criteria, contemporary marriage practices in Indonesia increasingly incorporate social variables such as education, economic status, and family background. Using a qualitative descriptive approach through literature review and document analysis, this research analyzes classical fiqh texts, the Compilation of Islamic Law (KHI), and empirical studies on marriage practices across different cultural settings in Indonesia. The findings reveal that kafā’ah remains relevant as a principle for ensuring marital harmony; however, its interpretation has shifted from lineage and socio-economic status toward shared values, emotional maturity, and religious commitment. The study also indicates a gap between normative legal frameworks and practical social considerations, influenced by cultural dynamics and modernization. This research contributes to contemporary Islamic family law discourse by highlighting the need for a contextual reinterpretation of kafā’ah that prioritizes ethical and spiritual dimensions over hierarchical social classifications.